Strategi Guru Dalam Mengatasi Kesulitan Pengenalan Dan Pencocokan Warna di TK Aisyah Bustanul Athfal 05 Medan - Lu’lu’ Ilmaknun; Fadhilah Salma Fauziah; Vivi Alaida Mahya (Institut Nalanda, 2024)
: This research aims to analyze fine arts learning in early childhood at Kindergarten Aisyiyah Bustanul Athfal 05 Medan, with a focus on coloring activities using gradation techniques. This research uses qualitative methods with interview techniques with one of the fine arts teachers at the kindergarten. The research results show that various fine arts activities, such as coloring using gradient techniques, making collages, and printing with natural materials, are carried out at Kindergarten Aisyiyah Bustanul Athfal 05 Medan. However, challenges in introducing colors to children still exist, so that some children experience difficulties in coloring activities. The role of teachers as guides and parental support is very important in developing children's artistic skills. This research recommends using varied environmental models to help children recognize colors better. Teachers can use color examples from nature and fine art to expand children's understanding of color. With this strategy, it is hoped that children can improve their ability to recognize and match colors, as well as develop creativity and imagination through fine arts activities